ELECTROCHEMICAL DEGRADATION OF REMAZOL RED RB 133 USING SACRIFICIAL ELECTRODES - Rekha, H B; Murthy, Usha N (MATTER: International Journal of Science and Technology, 2018)
Textile industries generate various types of wastewater depending on the industrial process and the raw materials used such as jute, cotton and animal fibers (wool and silk) and synthetic materials (nylon, polyester and acrylic). Dyeing and printing unit in textile processing industries use large volume of water (ranging from 200 to 250 kilo liter per ton of textiles) and different chemicals, dyes, and complex organic compounds make the textile wastewater very complicated to treat. In recent years, an alternative method to the conventional ones is the Electrochemical Treatment based on the generation of very reactive species such as hydroxyl radicals that oxidize a broad range of organic pollutants non-selectivity and quickly. The study aimed at the degradation of reactive dye by electro-coagulation using iron and aluminium electrodes.The results showed maximum color removal of 90.59% and COD removal of 54.36% operating at a current density of 176 A/m2 after electrolysis duration of 10 minutes at optimum pH 7 for iron electrode. Aluminum electrodes showed maximum color removal of 72.33% and COD removal of 56% after an electrolysis duration of 60 minutes, pH 7 at a current density of 216 A/m2. At the optimum conditions, the energy consumption, electrode consumption and operating cost to treat a cubic meter of sample found to be less for iron than aluminium electrode. The study concluded that, electro-coagulation proved to be an efficient method for the degradation of reactive red dye using iron electrode.